Estimated Number of Men Who Have Sex With Men With Indications for HIV Pre-exposure Prophylaxis in a National Sexual Network Study. (1st May 2020) - Weiss, Kevin M.; Prasad, Pragati; Ramaraju, Ramya; Zlotorzynska, Maria; Jenness, Samuel M.
Abstract : Background: A 2015 CDC analysis estimated that 24.7% of sexually active men who have sex with men (MSM) had indications for HIV pre-exposure prophylaxis (PrEP) based on 2014 US Public Health Service (USPHS) clinical practice guidelines. Given that the USPHS revised these guidelines in 2017, updated estimates of the fraction of MSM indicated for PrEP overall and stratified by demographic factors and geography are needed to scale-up PrEP for MSM in the US. Methods: We conducted a national web-based study of 4904 MSM aged 15–65 who had ever had sex with another man between July 2017 and January 2019. We estimated the percentage of HIV-negative, sexually active MSM meeting USPHS indications for PrEP by demographic category. Results: Of 3511 sexually active, HIV-negative MSM, 34.0% (95% confidence interval: 32.4 to 35.6) met USPHS indications for PrEP, with percentages consistent across US census region and varying slightly by race/ethnicity (Black: 32.2%, White: 33.7%, Hispanic: 36.4%, Other: 33.6%). Among individuals meeting USPHS PrEP indications, 93.5% reported condomless anal intercourse in the prior 6 months. Among all survey respondents, PrEP eligibility was lowest among non-Hispanic black (18.4%) and younger respondents (15–17: 4.1%; 18–24: 18.1%). Conclusions: Estimated percentages of MSM meeting indications for PrEP exceeded the previous CDC estimate across race/ethnicity, age, and census regions, with one-third of adult, sexually active, HIV-negative MSM exhibiting indications for PrEP. This study suggests, given current guidelines for PrEP indications, that a different fraction of eligible MSM could be receiving PrEP than previously estimated. Abstract : Supplemental Digital Content is Available in the Text.